The Effect of Audit Committee Expertise and Meeting on Earnings Quality in Indonesian Listed Companies: A Conceptual Approach - Surbakti, Lidya Primta; Shaari, Hasnah; Bamahros, Hasan Mohammed Ahmed (2017)
In recent years, the financial crisis and corporate scandals in the United States of America, Europe and Asia were the initial causes that brought up the issue of earnings quality in both Asian and other transitional economies. In fact, the main issue was centered on financial reporting manipulations and there is need to examine and develop a mechanism that will focus on monitoring and improving corporate governance through earnings quality.In particular, audit committee effectiveness is seen as a significant factor in ensuring effective corporate governance and in view of this, the aim of this paper is to develop a conceptual framework that will examine the impact expertise, meeting and meeting attendance on the earnings quality of companies. In addition, agency theory is expected to explain the above three factors in providing explanation to accounting information that relates to the earnings quality under study.Finally, it is expected that future empirical studies with this conceptual framework can enhance earnings quality for users of financial statements such as: investors, creditors, shareholders and other stakeholders in Indonesia and beyond.